Organizzare il tempo. Fasti e calendari a Roma e nell’Italia romana (Milano University Press, 2025)
In the Roman world, the calendar marked the rhythms of a community and defined on a daily basis the appropriate times for each activity, public and private. In the organization of the civic year in Rome as in the local communities of Roman Italy, the entry into office of the magistrates signalized the beginning of the new year and thus determined the sequence of public and private occasions (especially of a religious nature) that would then be celebrated during the following twelve months and that would mark the succession of the seasons. The studies collected in this volume address, from different perspectives and with an interdisciplinary approach, some of the many problems posed by the Roman calendar, by focusing on issues such as the (ever fluctuating) date of the beginning of the civic year, the local reception of festivals and rites celebrated in the city of Rome, the aspect and the rituals of some festivals celebrated during the year as well as their literary declination. Ultimately, it will be shown how the shared organization of time represented an indispensable aspect of the religious and civic life of a city.